Hj. Samuri Sate Kajang office automation using Lotus Notes application - Nadarajan, Vimala (2002)
The advances of modem computer technology today have prompted offices to automate their office processing. As businesses continue to expand, the need to automate office processes increases. It is vital to incorporate computer technology to remain competitive. The main object of this study is to create a working system capable of routing forms and saving data in the database. It is to collect information such as staff information and new branch addresses. It allows employees to request stationeries online where the processing and routing is done by the office system. It also has a discussion database that helps employees to communicate among themselves. The discussion database allows the placing of comments and notices for others to view. The system was built using Lotus Notes version 5, a powerful workflow tool. Graphics were modified using Sierra Home SnapShot Express. The text was written using both the in-built word processor of Lotus Notes and Microsoft Word 2000. This system simplifies work and allows for faster document processing. The system is kept open to allow future upgrades and modification.